PEMBERDAYAAN PELAKU UMKM DI DESA UBUNG KAJA MELALUI PELATIHAN PEMASARAN DIGITAL - Christina Ayu Maha Dewi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This community service study aims to empower micro, small, and medium enterprises (MSMEs) in Ubung Kaja Village through a digital marketing training program designed to address low levels of digital literacy and marketing practice. A mixed-method approach was employed, combining a one-group pre-test post-test design for the quantitative strand with observations and in-depth interviews for the qualitative strand. Ten MSME owners from food, fashion, craft, and services sectors participated in a two-day training covering digital marketing concepts, the use of social media (Instagram, Facebook), local marketplaces, and WhatsApp Business. The findings indicate a significant improvement in participants’ knowledge, evidenced by an increase in average scores from 55 (pre-test) to 85 (post-test), and an increase in the proportion of participants owning dedicated business social media accounts from 40% to 100%. Qualitative results show higher self-confidence, the emergence of peer learning, and additional customers obtained through online channels. These findings suggest that structured and context-sensitive training, supported by follow-up via a WhatsApp group, is effective in strengthening MSMEs’ digital marketing capacity. Nevertheless, limitations related to the short mentoring period and the absence of long-term financial impact evaluation highlight the need for extended and integrated programs. Overall, this initiative offers a replicable model of MSME empowerment for other village contexts.